Evaluation of the student learning preparation program in obtaining the DELF A2 French Language Certificate for high school students: the csf-ucla approach - Hidayah, Nursipah; Madani, Faisal; Priyanto, Sugeng (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to evaluate the effectiveness of a high school student preparation program in achieving the DELF A2 French Language Certificate using the CSF-UCLA model approach. This model assesses five main dimensions: assessment, planning, implementation, improvement, and certification. The research method used is descriptive evaluative with a mixed approach (quantitative and qualitative). The instrument developed includes 20 question items based on indicators from each dimension. The results of the study indicate that the program has been in accordance with the needs of students, the materials and learning methods are designed systematically, the implementation is effective, and there are improvements in strategies based on student feedback. In addition, students feel more confident and show an increase in exam simulation scores. These findings confirm that the CSF-UCLA approach can be a comprehensive and contextual evaluation tool in improving the effectiveness of foreign language certification preparation programs at the secondary education level.